A Comparative Study of Photobiological and Photophysical Characteristic of Meso-Tetraphenylporphyrin and Meso-Tetraphenylchlorin as Photosensitizers for Photodynamic Therapy - Asmiyenti Djaliasrin Djalil; Susanti; Fuji Marsela Erlita; Ari Fariz Mustafa; Alwani Hamad; Suwandri (Science and Technology Indonesia, 2022)
Photosensitizer modifications are needed to improve the performance of Photodynamic Therapy (PDT) for the treatment of cancer. This work appraised the photophysical and photobiological characteristics of tetrapyrrolic macrocycles. Meso-tetraphenylporphyrin (m-TPP) and meso-tetraphenylchlorin (m-TPC) represent non-reduced and reduced pyrrole rings tetrapyrrolic macrocycles, respectively. The absorption spectra of m-TPP and m-TPC were performed. The relative quantum yield of singlet oxygen (ΦΔ) was measured at two different pH (6.3 and 7.4) relative to chlorine e6. Dark toxicity was monitored using the MTT assay on breast cancer T47D and NIH 3T3 cell lines. In addition, the stability of the compounds under indirect sunlight was also observed. The absorption maxima of the Q1 band of both compounds are at a longer wavelength. The Q1 peak of a reduced pyrrole ring is more intense than the non-reduced pyrrole ring with the lowest energy transition undergoing a redshift. The singlet oxygen generations are higher at pH 7.4 for both compounds with them-TPC showed a higher relative singlet oxygen quantum yield. In addition, the photosensitizers are stable under indirect sunlight radiation. m-TPC has higher cellular uptake than m-TPP in both cell lines. The dark toxicity of m-TPC is higher than m-TPP in T47D cells. However, the opposite occurred in observing dark toxicity in the NIH 3T3 cell line. Our study concludes that the cellular uptake and ΦΔ can be enhanced by reducing the pyrrole ring of the tetrapyrrole macrocycle. Therefore, m-TPC proved to be a better photosensitizer than m-TPP.